When Extension and Rhetorical Engagement Meet: Framing Public Audiences for Agricultural Science Communication. Issue 4 (2nd October 2022) - Pigg, Stacey; Scheper, Lindsey Ray
ABSTRACT: This article reports from a qualitative case study exploring how a team of agricultural scientists framed their nonscientific audiences for science communication. Our results indicate communication audiences and strategies were shaped by state extension systems. As a result, we argue that technical communicators can contribute to agricultural science communication teams by modeling rhetorically engaged communication and building capacity for audiences overlooked by extension models most focused on economic impact.